2014
DOI: 10.1155/2014/815184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra-Articular Hyaluronic Injection on Postural Stability and Risk of Fall in Patients with Bilateral Knee Osteoarthritis

Abstract: Knee osteoarthritis is a common cause of disability which influences the quality of life. It is associated with impaired knee joint proprioception, which affects postural stability. Postural stability is critical for mobility and physical activities. Different types of treatment including nonsurgical and surgical are used for knee osteoarthritis. Hyaluronic acid injection is a nonsurgical popular treatment used worldwide. The aim of this study was to demonstrate the effect of hyaluronic acid injections on post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Then, in a prospective, randomized, placebo-controlled trial involving 63 patients with grade II-III knee OA, an increase in isokinetic strength and proprioception after infiltration with Hylan G-F 20 was demonstrated (31). Finally, another study including patients between 50 and 70 years old with bilateral knee OA verified an increase in postural stability and a decrease in the risk of fall in patients treated with HA infiltration compared to worsening conditions in those who received the placebo (32). It has been previously demonstrated that aspirating joint effusion and/or injecting a local anesthetic into the joint abolishes arthrogenic muscle inhibition (33-34).…”
Section: Discussionmentioning
confidence: 91%
“…Then, in a prospective, randomized, placebo-controlled trial involving 63 patients with grade II-III knee OA, an increase in isokinetic strength and proprioception after infiltration with Hylan G-F 20 was demonstrated (31). Finally, another study including patients between 50 and 70 years old with bilateral knee OA verified an increase in postural stability and a decrease in the risk of fall in patients treated with HA infiltration compared to worsening conditions in those who received the placebo (32). It has been previously demonstrated that aspirating joint effusion and/or injecting a local anesthetic into the joint abolishes arthrogenic muscle inhibition (33-34).…”
Section: Discussionmentioning
confidence: 91%
“…Early detection of dysfunction in system of balance is essential for prevention and implementation of procedures aimed at minimizing the risk of age-related falls, and also an important part of functional diagnostics and rehabilitation (Khalaj et al 2014). The ability to comprehensively and objectively assess the status of the balance system is essential for the effectiveness of therapy and for function-al balance abilities in sport.…”
Section: Introductionmentioning
confidence: 99%
“…A perda de controle postural nos indivíduos com OA pode estar associada à fraqueza muscular, à redução dos mecanismos proprioceptivos e à limitação da funcionalidade, consequências estas que destacam a necessidade do envolvimento do tornozelo, do quadril e do treino de marcha no tratamento do EP de indivíduos com OA, especialmente através de exercícios cinesioterapêuticos ativos 8,9,18 . Dois estudos 12,13 utilizaram técnicas cinesioterapêuticas ativas (exercícios de fortalecimento, propriocepção, equilíbrio, treino de marcha, alongamento), sendo que um 12 realizou o tratamento domiciliar e outro 13 utilizou a cinesioterapia por meio da wiiterapia (tratamento por meio de jogos eletrônicos).…”
Section: Discussionunclassified
“…Os aspectos supracitados podem atuar como fatores desencadeantes para impacto em diversos âmbitos da saúde do indivíduo com OA, como a qualidade de vida e a propriocepção articular. Esta última afeta diretamente a estabilidade postural, fundamental para a mobilidade e atividades da vida diária, gerando alterações no equilíbrio postural (EP) e risco de quedas [7][8][9][10][11] .…”
Section: Introductionunclassified